Urgent-Start Peritoneal Dialysis Catheter Placement: Comparative Study between Percutaneous Image-Guided versus Laparoscopic Techniques - Mahmoud, Khalid; Moawad, Sherif; Farrington, Crystal; Massoud, Moustafa; Gunn, Andrew; Li, Yufeng; Dai, Chen; Hamed, Basant Farouk; Almehmi, Ammar; Abdel-Aal, Ahmed Kamel (The Arab Journal of Interventional Radiology, 2019)
Objective: The objective of this study was to compare the outcomes and complications of percutaneous image-guided versus laparoscopic peritoneal dialysis (PD) catheter placement techniques in the urgent-start setting. Materials and Methods: The medical records of 273 patients who had their first PD catheter between November 2012 and May 2017 were retrospectively reviewed. Patients were divided into radiologic group (n = 26) and laparoscopic group (n = 16). Descriptive and Kaplan–Meier (KM) analysis were used to compare time to first complication, time to catheter removal, and patient survival between the two groups. Complication-free and catheter removal rates at 1, 3, and 12 months were estimated from KM analysis. Results: A total of 42 patients were included in the study. The baseline demographics were similar between the two groups. In the radiologic group, the estimated 1, 3, and 12 months' complication-free rate were 100%, 94%, and 67%, respectively, which was not significantly different from 93%, 85%, and 45%, respectively, in the laparoscopic group (P = 0.543). The rate of catheter complications was not significantly different between the radiologic group (50%) and the laparoscopic group (31%) (P = 0.3382). The catheter removal rate in the radiologic group was 8, 18%, and 38% at 1, 3, and 12 months, respectively, versus 0%, 8%, and 20%, respectively, in the laparoscopic group (P = 0.298). The overall patient survival between two groups was not significantly different (P = 0.116) with estimated patient mortality of 15.4% at 12 months in the radiologic group and no deaths in the laparoscopic group. Conclusion: Image-guided percutaneously placed PD catheters have a similar complication and removal rates compared to laparoscopically placed catheters in the urgent-start setting.
Keywords: Chronic kidney disease; end-stage renal disease; fluoroscopic; laparoscopic; peritoneal dialysis; urgent-start